[Afisz. Incipit] Stefan Jaracz : droga porywu i buntu ... (Gdańsk : [wydawca nieznany], 1951)
Afisz informujący o wykładzie o Stefanie Jaraczu i Ludwiku Solskim.
Keywords: Jaracz, Stefan -- (1883-1945).; Solski, Ludwik -- (1855-1954).; Gdańsk (Polska) -- 1945-1970 -- druki ulotne